Integrative clinical social work practice : a contemporary perspective - Barth, F. Diane (Essential Clinical Social Work Series, 2014)
In recent history the practice of medicine and mental health  has been increasingly  eclectic, as more and more practitioners harness seemingly disparate therapies and techniques to arrive at clinical breakthroughs. But while social work professionals have been involved in integrative practice informally and intuitively for years, resources to bring structure to this therapeutic concept have been few and far between. In response, Integrative Social Work Practice offers innovative ways of conceptualizing cases, communicating with clients, and making better therapeutic use of client individuality. Rich in research, evidence-based and clinical material from a variety of settings, the book begins with the basic organizing principles behind effective integrative practice. Real-world examples flesh out the theoretical rationales, and psychodynamic, cognitive, behavioral, and developmental methods are shown in practical context. The author also demonstrates how to balance flexibility and boundaries, and manage diverse and even conflicting theories, while providing clear guidelines on: Integrating key psychotherapeutic approaches into social work. Using somatic knowledge to enhance therapy. Making assessments and choosing interventions. Applying an integrative approach to therapeutic relationships. Creating manageable goals based on small steps. Building and working with an integrative team. An important step forward in both professional development and the larger therapeutic picture, Integrative Social Work Practice benefits researchers and practitioners as well as supervisors and students in social work and counseling.